Bicyclo[2.2.2]octane-1, 4-dicarboxylic acid: towards transparent metal–organic frameworks. Issue 23 (23rd May 2017) - Llabres-Campaner, P. J.; Pitarch-Jarque, J.; Ballesteros-Garrido, R.; Abarca, B.; Ballesteros, R.; García-España, E.
Abstract : The preparation of transparent porous materials can offer a different access towards the study of molecules under solid confined space. Abstract : The preparation of transparent porous materials can offer a different access towards the study of molecules under solid confined space. Metal–organic frameworks represent a unique opportunity due to their tunable pore size, however aromatic linkers present strong absorption and reduce the transparency. Herein, we report the first example of a MOF with bicyclic organic dicarboxylic linkers and its use as a solid solvent.